INTEGRATING CULTURE INTO ENGLISH LANGUAGE LEARNING: ENHANCING COMMUNICATIVE COMPETENCE AND FLUENCY - Madina Ulugbek kizi Muhammadova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study shows how language and culture are linked in the process of learning English. It looks at how cultural context makes people better at communicating, stops misunderstandings, and helps them understand the subtleties of language better. The integration of cultural elements is shown to be an important part of becoming truly fluent.